Isolation of soil Actinomycetes from Forest Park of Pocut Merah Intan as potential producers of antimicrobial compounds - Husnah Milda; . Suhartono; Cut Yulvizar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This study was undertaken to investigate soil Actinomycetes from grand forest park of Pocut Meurah Intan as well as to evaluate their potential to produce antimicrobial compounds. The study was conducted in Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, Syiah Kuala University from February to July 2012. The research was carried out by using an explorative method with laboratorial evaluation. Three different soil samples were taken from a depth of 10-20 cm below the soil surface and isolated on YM agar medium. During the investigation, 24 isolates were recovered and exhibited various morphological characteristics. The results of the antimicrobial assay showed that 14 isolates (58.33%) were active against one or more of the test organisms. Among the 14 active isolates, one isolate (7.14%) showed antibacterial activity; 9 isolates (64.29%) showed antifungal activity; and 4 isolates (28.57%)  exhibited a broad-spectrum activity against both of the test bacteria and fungi. The inhibitory activity were also varied, ranged from weak (5 mm), moderate (5-19 mm), to strong (20 mm).  The highest antimicrobial activity was presented by ATH-17 against Candida albicans (34.50 mm), while the lowest was exhibited by ATH-15 against Escherichia coli (0.20 mm).